Pancreatic non-functioning neuroendocrine tumor: a new entity genetically related to Lynch syndrome - Barrera, Anna Serracant; Pla, Sheila Serra; Blázquez Maña, Carmen María; Salas, Rubén Carrera; Monforte, Neus García; González, Natalia Bejarano; Monzonis, Andreu Romaguera; Navarro, Francisco Javier Andreu; Cueto, Maria Rosa Bella; Borobia, Francisco G. (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
Some pancreatic neuroendocrine tumors (P-NETs) are associated with hereditary syndromes. An association between Lynch syndrome (LS) and P-NETs has been suggested, however it has not been confirmed to date. We describe the first case associating LS and P-NETs. Here we report a 65-year-old woman who in the past 20 years presented two colorectal carcinomas (CRC) endometrial carcinoma (EC), infiltrating ductal breast carcinoma, small intestine adenocarcinoma, two non-functioning P-NETs and sebomatricoma. With the exception of one P-NET, all these conditions were associated with LS, as confirmed by immunohistochemistry (IHC) and polymerase chain reaction (PCR). LS is caused by a mutation of a mismatch repair (MMR) gene which leads to a loss of expression of its protein. CRC is the most common tumor, followed by EC. Pancreatic tumors have also been associated with LS. Diagnosis of LS is based on clinical criteria (Amsterdam II and Bethesda) and genetic study (MMR gene mutation). The association between LS and our patient’s tumors was confirmed by IHC (loss of expression of proteins MLH1 and its dimer PMS2) and the detection of microsatellite instability (MSI) using PCR.